Assessing the effectiveness of learning a complex motor activity in children aged 9-10 years - Matczak, Dawid; Wieczorek, Marta (Journal of Education, Health and Sport, 2022)
Introduction Learning is a complex and multi-dimensional process that depends on cognitive and emotional processes and the development of functional systems of the human body. One type of learning is motor learning. Its course and effects depend on many factors, one of the factors may be gender. Differences between intellectual and motor learning tend to be blurred when learning a complex motor activity takes place. Purpose The cognitive aim of the study is to assess the effectiveness (speed, efficiency, durability) of learning a complex motor activity in a selected group of girls and boys. Materials and methods: The study was conducted among 73 children (44 boys and 29 girls) aged 9 - 10 years. The teaching experiment method consisting of three stages was used. The research tool is a program of learning to juggle with three tennis balls. Learning speed was assessed using the Learning Speed Rate (LSR); efficiency was based on the results of subsequent stages as part of the experiment, whereas durability was evaluated on the basis of the effect compliance between stages of the experiment. Results: The speed, efficiency and durability of learning a complex motor activity in children participating in the study showed similar levels. Slow learning was dominant among both girls and boys. Yet, boys achieved better learning effects than girls, but these differences were not statistically significant. The subjects showed high durability of learning effects. Conclusions: The effectiveness of learning a complex motor activity is characterized by inter-subject variability. Gender makes distinction in terms of speed, efficiency and durability of learning a complex motor activity.